Meteorological drought quantification using standardized precipitation index for Gulmarg area of Jammu and Kashmir - AKHTER, TABASUM; PANDIT, B.A.; VISHWAKARMA, DINESH KUMAR; KUMAR, ROHITASHW; MISHRA, RAJAT; MARYAM, MUNJID (Journal of Soil and Water Conservation, 2023)
Drought is natural disaster which is characterized by intense and persistent shortage of precipitation. Drought monitoring plays an important role for the freshwater planning and management as well as for prediction of the onset and severity of droughts. The present study deals with the potential of using precipitation-based Standardized Precipitation Index to analyse the temporal pattern of drought in the Gulmarg area of Baramulla district of Jammu and Kashmir. Monthly precipitation data from 2010 to 2019 for Gulmarg region were used to compute Standardized Precipitation Index (SPI) values. The computation of SPI series was carried out for short, intermediate and for long time scales. The moderate drought occurred in 2013 and severe drought occurred in 2018. The intensity of these droughts was found to be moderate during three years from 2011-2013. The SPI values were less than (-)1.0 for these years on 6-month, 9-month and12-month time scales. The 12-month SPI value for these years were (-)1.05, (-)1.34, (-)1.49, respectively. The 12- month SPI values for 2018 was (-)1.56 which indicated severe drought. However, the SPI values suggest moderate dryness in place of acute dryness during the years of severe and extreme drought.